Global Africa. A Critical Genealogy of a Militant Concept - (:unkn) unknown (My University, 2022)
The terms "Global Africa" are increasingly used in various sectors such as art, fashion, services and academic research with the aim of representing the multiple connexions between Africa and the world. It seems therefore important to recall the radical origin of these terms. In fact, they directly come from the Pan African mobilization of the early 1990s around the claim for Reparations for slavery and colonialism. One step further, they can be almost exactly juxtaposed on the social and political history of Pan Africanism that is deployed over space and time. I adopt here a pedagogical approach by presenting two publications of reference (by Ali A. Mazrui and Michael O. West) and mobilizing references in various languages and from various disciplines. I analyse these terms in order to clarify the project and the struggle that has constituted them, and I propose a critical genealogy, from their militant emergence to their institutionalisation by the General History of Africa of UNESCO. The stake is crucial as we try to center Pan Africanism in the ways we think and represent the presence of Africa and Africans in our global world.
Keywords: African Research